What Triggers Prolonged Inflation Regimes? A Historical Analysis - Isabel Vansteenkiste (European Central Bank (ECB), 2009)
This paper empirically assesses which factors trigger prolonged periods of inflation for a sample of 91 countries over the period 1960-2006. The paper employs pooled probit analysis to estimate the contribution of the key factors to inflation starts. The empirical results suggest that for all cases considered a more fixed exchange rate regime and lower real policy rates increase the probability of an inflation start. For developing countries, other relevant factors include food price inflation, the degree of trade openness, the level of past inflation, the ratio of external debt to GDP and the durability of the political regime. For advanced economies, these factors turn out to be statistically insignificant but instead a positive output gap, higher global inflation and a less democratic environment were seen to be detrimental for triggering inflation starts. Finally, oil prices, M2 growth and government spending were never statistically significant.
Keywords: E31; E58; 330; emerging markets; inflation; Panel Probit; Inflation; Probit-Modell; Panel; Schwellenländer